Synthesis and in vitro delivery of plasmid-encapsulated chitosan nanoparticles in human kidney cancer cells as a vector for gene delivery - Cha, Yee Kuen (2015)
Chitosan has been extensively adopted in biomedical and pharmaceutical research due to its advantageous properties such as biocompatibility, low-toxicity, and biodegradability. These properties suggest chitosan as a robust material for numerous biomedical applications as gene and drug delivery systems. In this study, the synthesis and in vitro delivery of plasmid-encapsulated chitosan nanoparticles in human kidney cancer cells (786-O cell line) were reported. A modified ionic gelation system was utilized to synthesize spherical nanoparticles, and its ability for in vitro delivery of a plasmid containing a GFP reporter gene was evaluated. CNPs were characterized using Dynamic Light Scattering to analyze size distribution and polydispersity index, while Field Emission-Scanning Electron Microscopy was used to analyze surface morphology of the nanoparticles. The 786-O human kidney cancer cell line was then established and treated with CNP-pEGFP formulated at different incubation timepoints. Transfection of 786-O cells were performed by using blank media, CNP and plasmid alone and visualized under both bright-field and fluorescent microscope. FESEM images was found to correlate with DLS data, where the optimum nanoparticle size and PDI value was obtained at a chitosan: TPP ratio of 3:1. Transfection results showed that CNP and cells did not readily fluoresce, and successful GFP expression in cells were only achieved with CNP encapsulation. The results of cell transfection at two different time points showed positive GFP expression, suggesting that CNP was potentially an effective delivery system. However, optimizations are required to further increase efficiency of the gene delivery system for subsequent utilization in biomedical and pharmaceutical fields.